Literature Review On The Role Of Decision-Making System For Indonesian Workforce Recruitment In Industrial Revolution 4.0 - Sylvia, Sylvia (Jurnal Info Sains : Informatika dan Sains, 2024)
Industry 4.0 is impacting the world of work, increasing efficiency and effectiveness while posing challenges for human resource management in terms of talent acquisition. Automation and technological advancements require new skills for workers to remain competitive. However, surveys show that graduates in Indonesia do not have the skills and knowledge that match industry demands, resulting in a mismatch between labor supply and demand. Human resource professionals must adapt to the rapidly evolving industry by making effective and efficient decisions in the recruitment and selection process. Decision-making systems play an important role in optimizing this process, especially through the use of Analytical Hierarchy Process (AHP) in Industry 4.0 using big data and the internet. Through a systematic literature review, the potential of AHP in supporting decision-making for human resource selection/recruitment in the Indonesian workforce and Industry 4.0 is explored. AHP's ability to consider multiple criteria and weights among alternatives enables flexible and structured decision-making, making it a suitable tool for recruitment and selection processes.